Tauhi Vā, A Tongan Artistic Tradition Continues in Academic Research: A Book Review of Tēvita O. Ka‘ili’s Marking Indigeneity: The Tongan Art of Sociospatial Relations (2017) - Faleolo, Ruth (Lute) (Art/Research International, 2024)
I have purposefully used a narrative approach in my review of Ka‘ili’s (2017) Marking Indigeneity: The Tongan Art of Sociospatial Relations to support my meaning making as a Tongan academic and Pasifika researcher. I considered elements of the text that worked well for me as an early career researcher and that are accessible to Tongan and non-Tongan academics alike. The Oceanian artistic traditions of time (tā) and space (vā) promoted in this book offer a continuation of ancient oral traditions into the contemporary realm of academic literature. In essence, Ka‘ili’s book brings significant understandings of the tā-vā theory into interdisciplinary research spaces and across the global landscape of Pasifika research and academic practice. This is evidenced in the more than 60 Pasifika authors’ citations of Ka‘ili’s book, to date. My recommendation of this book draws upon these facets: the accessibility of the text, the elements of the text, and the global reach of the text.